Continental-scale assessment of the African offshore wind energy potential: Spatial analysis of an under-appreciated renewable energy resource - Elsner, Paul (Renewable & sustainable energy reviews, 2019)
Offshore wind energy is rapidly becoming a technology that developing countries could consider because project costs have recently fallen substantially. Further reductions are expected as the industry matures. For most African coastal states, specific information about their offshore wind potential is not available. This study aims to address this shortcoming by evaluating the technical offshore wind potential of the entire continent using spatially explicit models and long-term satellite data. Two different scenarios were developed to reflect different levels of technological maturity in the wind industry: The shallow-water, near-coast scenario 1 represented the conservative assumption that technology will not improve beyond what is available already now. The deep-water, full-exclusive economic zone (EEZ) scenario 2 assumes the operational availability of floating platforms that would allow it to access wind resources at much deeper water depths across the entire EEZ. It is emphasized that the model results are subject to a number of uncertainties and therefore should be treated as first order estimates only. Both scenarios indicate very good technical offshore wind energy potential for one third of the African coastal states, with Mozambique, South Africa, Somalia, Madagascar and Morocco exhibiting particularly good resources. More than 90% of the offshore wind resources are concentrated in coastal zones associated to three African Power Pools. These are the Southern African Power Pool (SAPP), the Eastern African Power Pool (EAPP), and the Comité Maghrébin de l′Electricité (COMELEC). A joint and integrated development within these power pools could offer a promising approach to utilising offshore wind energy in Africa. •Analysis of offshore wind energy potential for the entire African continent.•Results presented for all African coastal states.•One third of coastal states have very good offshore wind potential.•More than 90% of offshore resources concentrated in three African Power Pools.•Offshore wind energy could play important role in Africa's energy future.